Characterization of the adsorption of H2 and N2 on activated carbon used as an adsorbent in cryosorption pumps - Zobel, Nick; Wilfert, Stefan; Blaum, Klaus; Elbert, Sven; Mastalerz, Michael; Spiller, Peter J. (Journal of vacuum science & technology. B, Nanotechnology & microelectronics, 2025)
The adsorption behavior of H 2 and N 2 on two types of granular activated carbon, SC2 and Aquacarb 208C, was investigated in the cryogenic temperature range using automated high-vacuum gas adsorption measurements. The aim of the study was to identify a suitable material for potential use as an adsorbent in cryosorption pumps, as required for the SIS100 accelerator at the Facility for Antiproton and Ion Research in Darmstadt, Germany. To characterize the adsorption process, isotherms were measured and evaluated using several well-established theoretical adsorption models. These models enabled the determination of specific fundamental surface characteristics of the activated carbons, such as pore volume, pore surface, and adsorption energies. Among the models tested, the Dubinin-Radushkevich (DR-)theory best described the adsorption behavior of hydrogen on both adsorbents at subcritical temperatures and low pressures while enabling predictions under conditions relevant to cryosorption pumps. The DR analysis yielded temperature-independent pore volumes of 388  cm 3/g (STP) for SC2 and 417  cm 3/g (STP) for 208C. Based on this finding, the SIS100 cryosorption pumps were equipped with 208C as the adsorbent, with one pump exhibiting a maximum hydrogen uptake capacity of approximately 205 mbar l at 4.5 K.
Im Titel ist die Zahl "2" jeweils tiefgestellt
Gesehen am 27.01.2026